Hospital Inpatient Cost Optimization Using Activity Based Costing: A Case Study at RSUD Bantaeng - Dewita, Dewita; Syachbrani, Warka; Uluputty, Nurdjanna Fadjrin (Universitas Negeri Makassar, 2024)
Abstract. This study aims to evaluate the application of Activity Based Costing (ABC) in optimizing inpatient costs at RSUD Prof. Dr. H. M. Anwar Makkatutu Bantaeng. The ABC method is used to calculate costs based on activities occurring in the hospital, such as administrative services, patient care, and accommodation. The results show that cost calculations using ABC are more accurate and efficient compared to traditional methods. The inpatient service fees calculated with ABC are lower for Class I and III, while Class II is slightly higher. The cost differences between the ABC and traditional methods indicate that ABC provides a more realistic picture of cost allocation based on actual activities. This study offers valuable insights for hospitals in managing costs more efficiently and transparently. Keywords: Activity Based Costing (ABC); Cost Allocation Methods; Hospital Costs; Inpatient Cost Optimization; RSUD Bantaeng Abstrak. Penelitian ini bertujuan untuk mengevaluasi penerapan Activity Based Costing (ABC) dalam optimasi biaya rawat inap di RSUD Prof. Dr. H. M. Anwar Makkatutu Bantaeng. Metode ABC digunakan untuk menghitung biaya berdasarkan aktivitas yang terjadi di rumah sakit, seperti pelayanan administrasi, perawatan pasien, dan penginapan. Hasil penelitian menunjukkan bahwa perhitungan biaya dengan ABC lebih akurat dan efisien dibandingkan dengan metode tradisional. Tarif jasa rawat inap yang dihitung menggunakan ABC lebih rendah pada kelas I dan III, sementara kelas II sedikit lebih tinggi. Selisih biaya antara metode ABC dan tradisional menunjukkan bahwa ABC dapat memberikan gambaran yang lebih realistis tentang pembebanan biaya berdasarkan aktivitas yang sebenarnya. Penelitian ini memberikan wawasan penting bagi rumah sakit dalam pengelolaan biaya secara lebih efisien dan transparan. Kata kunci: Activity Based Costing (ABC); Biaya Rumah Sakit; Optimasi Biaya Rawat Inap; Perbandingan Metode Biaya; RSUD Bantaeng